WAIS Divide sulfate and nitrate isotopes - Alexander, Becky; Steig, Eric J. (IEDA: US Antarctic Program Data Center, 2017)
Abstract: This data set contain oxygen isotopes of sulfate and nitrate and nitrogen isotopes of nitrate from the WAIS Divide ice core from the surface to 577 m depth at varying resolution